Additional diagnosis, observations of breeding biology and tadpole of a little known dwarf puddle frog, Phrynobatrachus inexpectatus (Anura: Phrynobatrachidae) - Tiutenko, Arthur; Zinenko, Oleksandr (Salamandra, 2020)
Phrynobatrachus inexpectatus and P. minutus are sister species of dwarf-size puddle frogs endemic to humid montane forests in the Ethiopian highlands. For almost two decades P. inexpectatus was officially known only from two populations, although a wider distribution was assumed. We confirm a population of this species in Harenna Forest (Bale Zone), at 1,400-2,400 m a.s.l. and report observations of its ecology and breeding biology, including descriptions of its advertisement call and tadpole. Phrynobatrachus minutus was long believed to be distributed east of the Great Rift Valley in the same forested area, but we did not find any evidence of this species in the area surveyed. We discuss the misidentification of these species by previous researchers and replace P. minutus with P. inexpectatus in the amphibian species list of the Harenna Forest. An additional diagnostic description of P. inexpectatus is provided that should help to distinguish this species from P. minutus and from the sympatric members of the P. natalensis complex.
CRIS-Team WoS Importer:2020-06-05